Physical and physiological demands during handball matches in male adolescent players - Ortega-Becerra, M.; Belloso-Vergara, A.; Pareja-Blan, F. (Journal of Human Kinetics, 2020)
This study aimed to describe the physical and physiological demands of adolescent handball players and compare movement analysis and exercise intensities between the first and second halves and between the different periods of the match. Fourteen adolescent handball players (age 15.7 +/- 0.8 years, body mass: 65.6 +/- 3.4 kg, height: 169.5 +/- 3.9 cm), played two friendly matches, in which no substitutions were made. The analysis was carried out with a Global Positioning System technology. The following physical variables were analyzed: Total distance covered (TD); distance covered at faster velocities than 18 km.h-1 (TDC>18km/h number of accelerations (Accel) and decelerations (Decel); number of accelerations and decelerations higher than 2.78 m/s-2 (Accel>2,78 m.s-2 and Decel>2.78 m.s-2); number of sprints (Sprints); accelerations interspersed with a maximum of 30 s between them (RAS.30s) and as a physiological variable the heart rate (HR) was examined. Significant differences (p < 0.01 . p < 0.001) between the first and the second half in all variables mentioned were observed, except in Accel>2.78 m.s-2 and Decel>2.78 m.s-2. This trend was also observed when comparing performance between the different 10-min periods. The 5th period (period 40-50 minutes) was the one that showed differences with respect to the previous ones. Adolescent handball players showed lower levels of exercise intensity, assessed by both time-motion and HR data, in the second half of matches, especially in the middle of this period.